Thin Ferrite Wafer Uniformly Polished with Magnetic Attraction Method. (7th September 2020) - Wang, Jing; Ou, Lin; Hu, Pengfei; Wang, Guangcai
Abstract : When a ferrite substrate is used to prepare thin-film InSb Hall element chips, one surface of the ferrite wafer needs to be polished. The traditional chemical mechanical polishing (CMP) method, often used for polishing of ferrite wafers, has several problems: a long time to install and remove wafers, a little high debris rate, and high cost. Taking advantage of the fact that ferrite wafers can be magnetically attracted, a method using independent RuFeB magnets to attract and hold ferrite wafers is proposed. The polishing head holding the ferrite wafer can perform planetary rotary motion to achieve uniform polishing. The polishing head floats up and down freely on the polishing pad, without the requirements of matching and process accuracy in machining, mechanical linkage, and control. The roughness of the ferrite surface after polishing is about 0.18 μ m, which meets the requirements for the substrate of InSb Hall element chips. With no debris, the efficiency of installing and removing wafers is 30 times higher than that of traditional methods. At the same time, compared with traditional CMP machine, the cost of CMP equipment made by this method is very low.